Policy Formulation of Community-Based Sanitation Programs in Indonesia - Apriansyah Apriansyah; Fitri Kurnianingsih; Mahadiansar Mahadiansar (Jurnal Pemerintahan dan Kebijakan (JPK), 2022)
Cleanliness is an inseparable part that is the obligation of every individual for survival; in the conditions of the COVID-19 pandemic, stakeholders have prepared policies in the health sector so that people get their right to live healthily. This study intends to evaluate the role of the government in managing sanitation programs during the COVID-19 pandemic, where policies previously needed to formulate solid policies. This research method uses a literature study where data analysis uses relevant secondary data so that it can be analyzed in depth using the concept of the policy implementation process. The results show that in the sanitation program during the COVID-19 pandemic, the government's role in setting agendas must refer to existing problems in the form of community group routines. Furthermore, the government's policy formulation must take a community-based approach that provides insight into the importance of sanitation program involvement and legitimacy. Finally, an evaluation of government policies must make breakthroughs and program initiations in each regional stakeholder by prioritizing innovations that can happen by the Indonesian people.